TUTURAN TOLEA DALAM RITUAL PESTA ADAT MOSEHE WONUA SUKU TOLAKI MEKONGGA DI KABUPATEN KOLAKA: TINJAUAN SEMIOTIKA - Sultan, Sultan; Maknun, Tadjuddin; Said, M. Ikhwan (Universitas Hasanuddin, 2018)
This research is a qualitative descriptive study, Research location in Kolaka District, The data source is the meaning of the Kalo Sara symbol obtained from the Mekongga Mosehe Wonua custom ritual in Kolaka District, either words, phrases, or sentences. Duration of study, ie June 2015 to end of April 2016. The results of this study indicate that the first meaning of Tolea speech in every stage of the speech Tolaki Society in Mekongga Southeast Sulawesi make the speech disclosed Tolea at the beginning or opening speech is a symbol. The meaning In the opening speech is a symbol of respect. In the core speech is a symbol of obedience in ritual. In the closing speech of Tolea is a symbol of appreciation. The two functions of Tolea's utterance in the Mosehe Wonua ritual in Kolaka District, which contains a prominent religious significance in the Mosehe Wanua ritual ceremony of the Tolaki community in Mekongga Southeast Sulawesi is a form of public confidence in the influence of ancestors and customs in every procession